INSTRUCTIONAL DESIGN FOR THE TEACHING OF ENGLISHAT THE FIRST YEAR OF SMP N 3 SAWIT BOYOLALI: NATULISTIC STUDY - Trisari, Anggarani Dias, Prof. Dr. Endang Fauziati, M. Hum, Dr. Dwi Haryanti, M. Hum (2015)
This research aims at describing an instructional design for the teaching of English at the first year of SMP N 3 Sawit, Boyolali. The objective of this study is to describe an instructional design in the teaching English at SMP N 3 Sawit. In this research, there are eight components of instructional design in the teaching of English that the writer analyzes, namely: (1) learning objective, (2) classroom procedures, (3) classroom techniques, (4) role of instructional material, (5) teachers' role, (6) students' role, (7) role of media, and (8) evaluation model. The type of this study is descriptive research especially naturalistic study. The data are derived from event and informant. The methods of collecting data are observation, interview, and documentation. The techniques of analyzing the data are reduction of data, display of data and conclusion or verification. The result of this study shows that: (1) There are two learning objectives in the teaching English class namely: general objective and specific objective. The general objective is to develop the ability to communicate in English both in spoken and written form to deal with the development of science and technology in facing the globalization era. Specific objective can be differentiated for each language skill; there are speaking, listening, reading and writing. The specific learning objectives are difference in each skill based on the kinds of text, namely: transactional, interpersonal and monologue text. (2) The classroom procedure is based on Indonesian version of the 2006 curriculum's model there are exploration, elaboration and confirmation (EEC). (3) The classroom technique during exploration cycle such as instructor-initiated question or probes, oral repetition and advances organizer. During elaboration cycle such as role playing, answering question and discussing a topic or question. During confirmation cycle such as peer-editing and instructor's feedback. (4) The roles of instructional material are printed material and comprise both of printed and unprinted sources. Printed material as a reference source for students on grammar, vocabulary, pronunciation, and so on whereas both of printed and unprinted source as help the students to more understand what the topic will learn in the class and as a source of actively for students practice and communicative. (5) Teacher's role in the teaching learning process are teacher as controller, as organizer, as assessor, as prompter, as participant, as resource, as tutor, and as observer. (6) The student's role are the learner is monitor and evaluator of their own progress, learner is a member of a group and learns by interacting with others, and also learner learns from the teacher, from other students and other teaching sources. (7) The media used by teachers are picture and images, board and video. Picture, images and board as a visual media whereas video as an audio visual media. (8) The evaluation model used by teachers are daily examination, mid test and final test.